IMPLEMENTASI PENDIDIKAN KARAKTER SOSIAL MELALUI SEDEKAH JUM’AT DI UPTD SDN 05 BARUAH GUNUANG - Hayatus Syfa; Ulva Rahmi; Imdrawati (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This research aims to see how the social character education of students is implemented through the friday alms program at UPTD SDN 05 Baruah Gunuang. This research uses a descriptive qualitative approach with data collection tecniques through observation and interviews. The results of the research show that implementation of social character education through friday alms can run well. Because educators can carry out their role in accordance with competence and cooperation in social character education, so that later it can be applied by students not only in the school environment but also in the family and community.